2016
DOI: 10.3171/2016.3.spine151525
|View full text |Cite
|
Sign up to set email alerts
|

Posterior lumbar interbody fusion with cortical bone trajectory screw fixation versus posterior lumbar interbody fusion using traditional pedicle screw fixation for degenerative lumbar spondylolisthesis: a comparative study

Abstract: OBJECTIVE Several biomechanical studies have demonstrated the favorable mechanical properties of the cortical bone trajectory (CBT) screw. However, no reports have examined surgical outcomes of posterior lumbar interbody fusion (PLIF) with CBT screw fixation for degenerative spondylolisthesis (DS) compared with those after PLIF using traditional pedicle screw (PS) fixation. The purposes of this study were thus to elucidate surgical outcomes after PLIF with CBT screw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 11 publications
5
106
1
Order By: Relevance
“…In clinical practice, adults with degenerative lumbar spondylolisthesis treated with cortical bone trajectory pedicle screws or conventional trajectory pedicle screws attained statistically equivalent patient-reported outcomes and fusion rates. 18 Insertional torque was found to be almost twice as high for the cortical bone trajectory pedicle screws than for traditional trajectory pedicle screws. 13 In another study 23 of 79 adults with degenerative lumbosacral disease, the authors demonstrated that the use of cortical bone trajectory pedicle screws was associated with acceptable operative outcomes with a low complication rate.…”
Section: Discussionmentioning
confidence: 91%
“…In clinical practice, adults with degenerative lumbar spondylolisthesis treated with cortical bone trajectory pedicle screws or conventional trajectory pedicle screws attained statistically equivalent patient-reported outcomes and fusion rates. 18 Insertional torque was found to be almost twice as high for the cortical bone trajectory pedicle screws than for traditional trajectory pedicle screws. 13 In another study 23 of 79 adults with degenerative lumbosacral disease, the authors demonstrated that the use of cortical bone trajectory pedicle screws was associated with acceptable operative outcomes with a low complication rate.…”
Section: Discussionmentioning
confidence: 91%
“…Mori et al showed that mean post-operative and latest follow-up JOA scores were significantly increased from mean pre-operative scores in patients who underwent CBT [15]. Sakaura et al investigated JOA scores in patients who underwent CBT, pre-operative and post-operative JOA scores were significantly improved when compared [16]. In both our group, we have get the same result in the final follow-up.…”
Section: Discussionsupporting
confidence: 63%
“…The superior pullout strength, higher insertional torque and satisfactory stability of the screw-rod construction compared to the traditional fixation have been confirmed by biomechanical studies [7,10,[12][13][14][15][16][17][18]. And the comparable clinical outcomes, less multifidus muscle damage and less complications associated with instrumentations compared to PS have been observed in clinical studies [19][20][21][22][23][24]. However, the CBT screws placement accuracy, surgical parameters and complications in one surgeon's learning curve could rarely be found in literature.…”
Section: Introductionmentioning
confidence: 73%